A Comprehensive Review on the Traditional Uses, Phytochemical Compositions and Pharmacological Properties of an Ethnomedicinal Herb, Paederia foetida - Barai, Samir; Roy, Subhrajyoti; Bhattacharyya, Shubham; Hore, Mayukh (Current Traditional Medicine, 2025)
BackgroundPaederia foetida L. (Family - Rubiaceae) is a common herb found available in the temperate and tropical Asia. The ethnomedicinal applications of this plant are widely elaborated In Chinese Traditional Medicine, Ayurveda, and other ancient scriptures throughout the world. Different ethnic groups use this plant in the treatment of alimentary and digestive disorders, bone related diseases like rheumatoid arthritis, bone fractures as well as in the ailments of diabetes, coughs, asthma, itches, wounds, body ache, toothache, cancer etc.ObjectivesThis comprehensive review aims to provide an insightful understanding of traditional uses, chemical composition, and pharmacological properties of P. foetida (from 1976 up to 2023), which may provide a foundation for further study and for the proper utilization of P. foetida resources.MethodsLiterature survey was conducted using known databases and the relevant keywords.ResultsP. foetida has been widely used in Chinese traditional medicine (CTM) for the treatment of dyspepsia, jaundice, pains, diarrhea and others. Several ethnic groups throughout the world used this plant to cure common health complaints namely, abdominal pain, gastritis, dysentery, diarrhoea, constipation, joint pain, etc. A total of 24 bioactive phytocompounds, such as asperuloside, paederosidic acid, sitosterols, stigmasterol, campesterol, ellagic acid, iridoids, ursolic acid, epifriedelinol, and others are reported to possess antiulcer, antidiarrheal, antihyperglycemic, antioxidant, antitussive, anthelmintic, and hepatoprotective activities.ConclusionThe present review not only summarizes the alternative approaches using this herb by ethnic people for treating various disorders, but also focuses on the latest scientific investigations to elucidate different bioactivities of this plant, thereby facilitating the understanding of its correlation with contemporary pharmacology. However, till date, very few studies elucidated the biological properties of these phytochemicals that were isolated exclusively from this particular plant. Moreover, the correlation between phytocompounds from P. foetida and its pharmacological activities aiming towards clinical drug development is still lacking. Finally, further research should be oriented towards determining the optimal dosage and toxicological limits, and thereby providing guidance for clinical applications.
Keywords: pharmacology